Perbandingan Return dan Volatilitas Saham Bank Konvensional dan Syariah di Indonesia dengan Model GARCH(1,1) - Romaito Br Silalahi; Nico Berlinson Fernando; Diah Ayu Saptyaningtyas; Nikmatul Ajizah Ambao (Pendidikan Matematika FKIP Universitas Mataram, 2026)
This study compares the return and volatility of conventional bank stocks (equal-weighted portfolio: BBCA, BBNI, BBRI, BBTN, BMRI, ARTO) and Islamic bank stock (BRIS) listed on the Indonesia Stock Exchange over the period 2022–2026 using the GARCH(1,1) model. BRIS outperforms in terms of return (+0.0226%/day; cumulative +21.58%) but exhibits higher volatility (2.5102% vs. 1.5527%) and greater shock sensitivity (α = 0.1840 vs. 0.0682). Conventional banks show stronger volatility persistence (α + β = 0.9779; half-life 7.32 days) compared to BRIS (α + β = 0.9029; half-life 2.10 days). Both segments exhibit fundamentally different risk-return profiles, while their moderate correlation (ρ = 0.4488) suggests meaningful portfolio diversification opportunities.